Analisis Harga Pokok Produksi dan Harga Pokok Penjualan Berbasis Metode Full Costing pada UMKM Kolang Kaling MutiaraAnalysis of Cost of Production and Cost of Goods Sold Based on the Full Costing Method in MSMEs of Kolang Kaling Mutiara: Analysis of Cost of Production and Cost of Goods Sold Based on the Full Costing Method in MSMEs of Kolang Kaling Mutiara - Naurah Azka Kamila; Sarah Syawalia Hadi; Zahra Septentia Alminati; Mala Aspiatu Zahroh; Nisrina Nadhifah (PT Cakrawarti Empat Proksi, 2026)
The MSME sector plays a crucial role in the national economy, yet it often faces obstacles in financial management, particularly regarding the accuracy of capital calculations. This study aims to analyze the comparison of Cost of Goods Produced (COGP) and Cost of Goods Sold (COGS) calculations between the manual method applied by the business owner and the full costing method at MSME Kolang Kaling Mutiara. The research method used is descriptive qualitative, with data collection techniques through in-depth interviews, operational observation, and documentation. The analysis focuses on identifying raw material costs, supporting material costs, and factory overhead costs that are often overlooked by small business owners. The research findings indicate that the owner's manual calculation tends to be undervalued by IDR 285,000, with the manual COGP at IDR 314,500 compared to the full costing method which reaches IDR 599,500. This occurs because the business owner has not calculated equipment depreciation costs in detail and overlooks the allocation of operational costs for gas and electricity energy. The application of the full costing method successfully reveals these hidden costs, resulting in a more accurate COGP value that reflects the actual sacrifice of resources. The implication of this research is the importance of cost accounting standardization for MSMEs to avoid hidden losses and support more competitive and sustainable selling price determination.